Dual-purpose winter cereal mixtures for whole plant silage (Research, Society and Development, 2022)
Ensiling is an essential technique for animal production due to the seasonality of forage production during the year. The use of winter cereals is an economic and environmentally viable alternative because it uses idle areas in winter. The mixture of winter cereals for silage meets the need to extend the harvest period, reduce risks and improve the cost/benefit ratio for the producer. The experiment took place in 2020, with the objective of evaluating the feasibility of use and the chemical characteristics of the resulting silages, and leaf/stem/ear or panicle partition of the cultivars studied. The first part of the research was carried out in the field, in the experimental area of Embrapa Trigo in Passo Fundo - RS, in randomized blocks and three repetition, with four wheat cultivars (BRS Pastoreio, BRS Tarumaxi, BRS Tarumã and Tbio Energix 201), and one cultivar of black oat (Embrapa 139 – Fog). The second part took place in a place sheltered from rain, sun and extreme temperature variations, in a completely randomized design. The treatments were PVC silos containing the silages of the aforementioned cultivars and the mixtures Tbio Energix/Embrapa Neblina, BRS Tarumã/BRS Pastoreio, BRS Tarumaxi/BRS Pastoreio, Tbio Energix/BRS Pastoreio, and a mixture of two barley cultivars (BRS Quaranta/BRS Korbel). All silages showed adequate fermentative profile and satisfactory nutritional characteristics. The Pastoreio wheat cultivar can be mixed with Energix, Tarumã and Tarumaxi wheats, extending the harvest period by 15 days, with greater participation of leaf blades.